Madrasah Principal Communication Strategy In Improving Madrasah Management Effectiveness In State Tsanawiyah Madrasah 1 Deli Serdang Regency - Adyanto, Poniman; Rafida, Tien; Mesiono, Mesiono (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
Study This is aiming for analyzing communication strategies of the head of madrasah in increasing effective management at State Junior High School 1, Deli Serdang Regency. The main focus of the study covers conceptualization and communication of the head of madrasah, implementation of function management in communication strategy, the impact of communication strategy on effective management, as well as factors that support and inhibit increased effectiveness in madrasah management. The research method used is a qualitative approach with techniques of data collection through observation, interviews, and analysis of documents. Research This applies data validity tests through credibility, transferability, dependability, and confirmability. The results of the study show that (1) the head of the madrasah has good understanding about communication, strategy, conceptualization, and realizing the importance of communication in an organization, which is implemented in a way that is effective for building harmonious relationships. (2) Function management is running optimally, supporting achievement of the purpose of the madrasah in general efficiently and effectively. (3) Implications of communication strategies proven to increase performance in institutions, relationships between stakeholders, motivation and satisfaction, and create a positive organizational culture. (4) Underlying supporting factors for success include strong leadership, support staff, facilities, adequate communication, and competence in good communication. On the other hand, the factor inhibitor covers lack of understanding about communication, barriers to interpersonal communication, limited communication skills, and a high work burden. The solution covers improvement awareness, development skills communication, formation channel effective communication, and utilization of technology information. Conclusion of study This shows that the communication strategy of the head of the madrasah plays an important role in increasing the effectiveness of management at State Junior High School 1, Deli Serdang Regency.